Development of an automated, interference-free, 2D-LC–MS/MS assay for quantification of a therapeutic mAb in human sera. (4th July 2018) - Sucharski, Filip K; Meier, Simon; Miess, Christian; Razavi, Morty; Pope, Matt; Yip, Richard; Anderson, N Leigh; Pearson, Terry W; Warren, Andrew Paul; Krantz, Carsten
Aim: Hybrid LC–MS/MS assays are increasingly used to quantitate proteins in biological matrices. These assays involve analyte enrichment at the protein level. Although suitability has been demonstrated, they are limited by the lack of appropriate affinity reagents and may suffer from interferences caused by binding proteins or antibodies.Results: An online stable isotope standards and capture by anti-peptide antibodies assay was developed, which involves tryptic digestion of a therapeutic monoclonal antibody in human serum to destroy interfering proteins followed by enrichment using high affinity peptide antibodies. The assay was validated and compared with a standard ligand-binding assay currently used for quantification.Conclusion: The data show that the stable isotope standards and capture by anti-peptide antibodies-2D-LC–MS/MS assay can be used as an alternative method for measurement of monoclonal antibodies in clinical samples.